Structural properties of β-metal(II) hydroxides: Combined XAS and Raman spectroscopic studies on lattice stability. (26th July 2018) - Marini, C.; Olszewski, W.; Ramanan, N.; Joseph, B.; Simonelli, L.; Postorino, P.
Abstract: Temperature-dependent x-ray absorption (XAS) and high-pressure (HP) Raman spectroscopy results on two prominent β -metal(II) hydroxides, viz . β -Ni(OH)2 and β -Co(OH)2 are presented. Raman data at ambient conditions show the β -Co(OH)2 phonons to be softer than the β -Ni(OH)2 ones. Analysis of the extended x-ray absorption fine structure data at metal K -edge as a function of temperature reveals the Einstein frequencies of the metal-oxygen and the metal-metal bonds to be, respectively, 309 and for β -Co(OH)2 and the same to be 385 and for β -Ni(OH)2 . In both the β -metal(II) hydroxides, up to about 10 GPa, HP Raman spectroscopy show a continuous hardening of the phonon modes associated with the metal-oxygen sub-lattices, whereas a systematic frequency softening is displayed by the hydroxyl symmetric stretching mode. These contrasting behaviours imply a gradual development of lattice instability with pressure mainly due to the displacement of H atoms around the metal-oxygen axis. The presented data allow a direct comparison of the local-lattice behaviour by quantifying the strength (XAS) and anharmonicity (RAMAN) of the atomic bonds in the two systems.